Complications of Transrectal Prostate Biopsy - Cech P.; Luptak J. (Acta Medica Martiniana, 2014)
Objective: The aim of our study is to evaluate complications In patients who underwent a Transrectal Ultrasound Guided Prostate Biopsy (TRUS BP) at the Department of Urology of JFM CU and UHM in 2007-2008 and at the Department of Urology in Bojnice Hospital in 2009-2012.